USING CONCEPT MAPS TO ASSESS SCIENCE KNOWLEDGE OF PRE-SERVICE ELEMENTARY METHODS STUDENTS - Robert K Kuech (European Scientific Journal, ESJ, 2014)
The purpose of this study was observing the initial state of the pre-service elementary students’ content knowledge in science. Concept maps are designed to demonstrate the prior knowledge students have acquired around a variety of topics (Ruiz-Primo & Shavelson, 1996) as well as providing a valid assessment tool that is respectful of nontraditional learners who may have previously avoided the topics being assessed due to lack of understanding (Hough et al. 2007). Pre-service students were given a blank sheet of paper and asked to make a concept map with science as the central node. The results indicate that elementary pre-service students have less breadth and less organized science content knowledge than their secondary counterparts.